Direct and indirect photolysis of the antibiotic enoxacin: kinetics of oxidation by reactive photo-induced species and simulations - Lastre-Acosta, Arlen Mabel; Barberato, Bruna; Parizi, Marcela Prado Silva [UNESP]; Teixeira, Antonio Carlos Silva Costa (Springer Nature, 2018)
The purpose of this study was to investigate the aqueous phase photochemical behavior of enoxacin (ENO), an antibiotic selected as a model pollutant of emerging concern. The second-order reaction rate constants of ENO with hydroxyl radicals (HO●) and singlet oxygen (1O2) were determined at pH 3, 7, and 9. Also, the rate constants of the electron transfer reaction between ENO and triplet states of chromophoric dissolved organic matter (3CDOM*) are reported for the first time, based on anthraquinone-2-sulfonate (AQ2S) as CDOM proxy. The sunlight-driven direct and indirect ENO degradation in the presence of dissolved organic matter (DOM) is also discussed. The results show that direct photolysis, which occurs more rapidly at higher pH, along with the reactions with HO● and 3AQ2S*, is the key pathway involved in ENO degradation. The ENO zwitterions, prevailing at pH 7, show kENO, HO●, kENO,1O2, and kENO,3AQ2S* of (14.0 ± 0.8) × 1010, (3.9 ± 0.2) × 106, and (61.5 ± 0.7) × 108 L mol−1 s−1, respectively, whose differences at pH 3, 7, and 9 are due to ENO pH-dependent speciation and reactivity. These k values, along with the experimental ENO photolysis quantum yield, were used in mathematical simulations for predicting ENO persistence in sunlit natural waters. According to the simulations, dissolved organic matter and water depth are expected to have the highest impacts on ENO half-life, varying from a few hours to days in summertime, depending on the concentrations of relevant waterborne species (organic matter, NO3−, NO2−, HCO3−).
Keywords: Antibiotics; Direct and indirect photodegradation; Dissolved organic matter; Enoxacin; Environmental photochemical fate; Mathematical modeling; Reactive photo-induced species